PENGARUH LATIHAN SPLIT SQUAT JUMP TERHADAP POWER OTOT TUNGKAI PADA PESILAT TAPAK SUCI PONDOK MODERN AL-KAUTSAR PEKANBARU - ramadhan, Ichsan; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is that the kicks are not perfectly coordinated, and do not have the strength so that the kicks are easily read by opponents so that they are easily deflected, evasive and captured are related to the majority of students who research silat extracurricular activities and reduce physical training given to students specifically to train the strength of students' limbs which are useful when performing pencak silat. The purpose of this research was to research the effect of split squat jump training on leg muscle strength in the pesilat holy sites of Pondok Modern Al-Kautsar Pekanbaru. Based on the population and sample in this research were Participants of Tapak Suci College Modern Pondok Al-Kautsar Pekanbaru, the total number of students was 10 students. The instruments used to collect data were pre test and post test of leg muscle explosive power with a vertical jump test. The data analysis technique used is the t test. Based on the results of the pree test and post-test vertical jump with an average value of 14.40% with t test = 12.531> of t table = 1.833. Therefore, it can be used to divide split squat jump on leg muscle strength at the Pesantren Tapak Suci Modern Islamic Boarding School Al Kautsar Pekanbaru.Key Words: Split Squat Jump Training, Leg Muscle Power